Effect of Smoking on Antiplatelet Action of Clopidogrel in Patients with Ischemic Heart Disease - Nawaz, Usman; Noor, Mudassar; Khan, Waqar Aslam; Bakhtiyar, Salman; Nawaz, Amina (Pakistan Armed Forces Medical Journal, 2024)
Objective: To explore relationship between smoking and antiplatelet action of Clopidogrel in patients with ischemic heart disease (IHD).Study Design: Quasi-experimental studyPlace and Duration of Study: Department of Pharmacology, Army Medical College, National University of Medical Sciences, Rawalpindi, Pakistan from Aug 2015 to Dec 2019.Methodology: The quasi experimental study was carried out on 390 patients with IHD recruited through convenience sampling. Patients were placed in two groups. Group-1 included smokers while group-2 patients were nonsmokers. Blood samples of smokers (n=151) and nonsmokers (n=239) IHD patients were taken. Platelet function testing of all the samples was done through light transmission aggregometer (LTA) using adenosine diphosphate (ADP) as an agonist.Results: Among patients of IHD 82.12% of the smokers on Clopidogrel therapy were Clopidogrel responders and 17.88% were Clopidogrel resistant, while in nonsmoker group 70.71% patients were Clopidogrel responders and 29.29% were Clopidogrel resistant. There was a significant difference in Clopidogrel response status between smokers and nonsmokers, p=0.011. Furthermore, mean platelet aggregation of smokers was significantly lower than that of nonsmokers, p=0.004.Conclusion: Smoking can enhance antiplatelet effect of Clopidogrel in IHD patients with greater platelet inhibition and lesser chances of Clopidogrel resistance.